Pengaruh Media Pembelajaran Berbasis Teknologi dalam Pembelajaran Fisika SMA - Jihan Fadhilah; Dinni Epri Anggraeni; Jafar Akmaludin; Muhammad Ikhsan; Mega Cantika; Rina Hidayati Pratiwi (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to examine the effect of the use of technology-based learning media on the teaching process of Physics at the Senior High School level. The focus of the study includes improving conceptual understanding, learning motivation, and the development of 21st-century skills such as critical thinking and problem-solving. The method used is a literature study by analyzing various accredited scientific articles published between 2021 and 2025. The results of the study indicate that the integration of various digital media—such as PhET simulations, interactive media (Canva, Powtoon), animated videos, Augmented Reality (AR), and Android-based media—has a significant and consistent positive impact on student learning outcomes. Technological media has been proven to be able to visualize abstract Physics concepts more concretely, increase active engagement, and foster student learning independence. Thus, the use of digital media is an effective solution in overcoming the challenges of learning Physics that have been considered difficult by high school students.